Carbon Based Titania Photocatalysts - Ghosh, Trisha; Oh, Won-Chun (Asian Journal of Chemistry, 2012)
Photocatalytic degradation has always been an active field of research interest for scientific studies, which started almost three decades ago. Photocatalysis, not only is considered to be a promising method to revert the detrimental effects of organic pollutants, dyestuff and various other pollutants in air and water, but also has emerged as a promising way for the fabrication of semiconductor devices, solar cells, etc. So far photocatalytic purification of water by irradiation of titanium dioxide (TiO2) particles has proven to be an effective way of mineralization of pollutants. Carbon based titania photocatalyst demonstrated its excellent photocatalytic activity and has been increasingly investigated for further improvement. This review highlights the photocatalytic effect of TiO2 as well as the use of carbon based substances like, activated carbon, activated carbon fiber, fullerenes (C60), carbon nanotubes, graphene as support materials for TiO2 photocatalysis.